Congenital smooth muscle hamartoma. - Milano, A. (European Journal of Pediatric Dermatology, 2016)
Congenital smooth muscle hamartoma (CSMH) originates from the erector muscles of the hair; it does not tend to increase but rather with time the infiltration and hypertrichosis become less obvious. When hypertrichosis lacks CSMH should be differentiated from hemangioma and mastocytoma; deep hemangioma is warmer than normal skin, it is often crossed by telangiectasia and tends to increase in the first months; in mastocytoma swelling due to rubbing does not appear immediately and does not disappear in seconds. When there are hypertrophic hairs CSMH should be differentiated from congenital melanocytic nevus which has usually a darker complexion and is covered by hypertrophic hairs after the first year, from hairy nevus in which the skin is normally pigmented and not infiltrated and from Becker’s nevus where hypertrophic hairs appear in peripubertal period. In all these cases and in nevoid neurofibroma histological examination is diriment.